1993
DOI: 10.1152/ajprenal.1993.265.1.f35
|View full text |Cite
|
Sign up to set email alerts
|

V2-like vasopressin receptor mobilizes intracellular Ca2+ in rat medullary collecting tubules

Abstract: Cytosolic free calcium concentration ([Ca2+]i) was measured in single microdissected rat medullary collecting tubules [outer (OMCD) and inner (IMCD)] to identify receptors involved in vasopressin (AVP)-induced [Ca2+]i increases. In both segments, [Phe2,Orn8]vasotocin ([Phe2,Orn8]VT), a specific V1 agonist, as well as the V2 agonist 1-desamino-8-D-AVP (dDAVP) triggered [Ca2+]i variations. In OMCD, the mean response to 10 nM AVP roughly corresponded to the sum of V1 and V2 agonists effects. In IMCD, dDAVP (10 nM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 0 publications
4
51
0
Order By: Relevance
“…7). A similar dual coupling mechanism has been postulated for the V2 receptor in the rat medullary collecting duct [11,14,24]. Further more, Zhu et al [36] have demonstrated that, when overexpressed in vitro, the human V 2 receptor has the capacity to couple to both adenyl cyclase and phosphoinositide-specific PLC.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…7). A similar dual coupling mechanism has been postulated for the V2 receptor in the rat medullary collecting duct [11,14,24]. Further more, Zhu et al [36] have demonstrated that, when overexpressed in vitro, the human V 2 receptor has the capacity to couple to both adenyl cyclase and phosphoinositide-specific PLC.…”
Section: Discussionmentioning
confidence: 58%
“…This effect was independent of cAMP, since it was not mimicked by forskolin. Interestingly, cAMP-independent effects of dDAVP on [Ca2*]j have also been report ed for microdissected rat outer and inner medullary col lecting tubules [11,14,241. Similarly, AVP evoked a transient increase in [Ca2*^ in the complete absence of external Ca2+.…”
Section: Discussionmentioning
confidence: 77%
“…Coupling of V2Rs to adenylyl cyclase takes place after AVP binding and increases catalysis of ATP into cAMP, activating protein kinase substrates (e.g., PKA). An increasing understanding of the modalities involved in V2R signaling indicates that V2R also increases intracellular Ca 2ϩ (20,33,106,133). Furthermore, V2R-mediated AQP2 trafficking is now known to be calmodulin dependent (23).…”
Section: V2r Compared With Other Receptors In the Avp/ot Familymentioning
confidence: 99%
“…Double wavelength measurements of Fura-2 fluorescence were carried out after a 30-minute equilibration period with a standard photometric set up (model MSP 21) assisted by a microcomputer (51). As a rule, all tubules were studied within less than 1 hour following their microdissection.…”
Section: Cytosolic Ca Measurementmentioning
confidence: 99%